Trait and Marker Associations in Oryza nivara and O. rufipogon Derived Rice Lines under Two Different Heat Stress Conditions - Prasanth, V. Vishnu; Babu, M. Suchandranath; Basava, Ramana K.; Tripura Venkata, V. G. N.; Mangrauthia, Satendra K.; Voleti, S. R.; Neelamraju, Sarla (Frontiers in Plant Science, 2017)
Wild species and derived introgression lines (ILs) are a good source of genes for improving complex traits such as heat tolerance. The effect of heat stress on 18 yield traits was studied in four treatments in two seasons, under field conditions by subjecting 37 ILs and recurrent parents Swarna and KMR3, N22 mutants, and wild type and 2 improved rice cultivars to heat stress using polycover house method in wet season and late sowing method in dry season. Normal grown unstressed plants were controls. Both correlation and path coefficient analysis showed that the major contributing traits for high yield per plant (YPP) under heat stress conditions were tiller number, secondary branches in panicle, filled grain number, and percent spikelet fertility. Three ILs, K-377-24, K-16-3, and S-148 which gave the highest YPP of 12.30–32.52 g under heat stress in both the seasons were considered the most heat tolerant. In contrast, K-363-12, S-75, and Vandana which gave the least YPP of 5.36–10.84 g were considered heat susceptible. These lines are a good genetic resource for basic and applied studies on heat tolerance in rice. Genotyping using 49 SSR markers and single marker analysis (SMA) revealed 613 significant marker- trait associations in all four treatments. Significantly, nine markers (RM243, RM517, RM225, RM518, RM525, RM195, RM282, RM489, and RM570) on chromosomes 1, 2, 3, 4, 6, and 8 showed association with six traits (flag leaf spad, flag leaf thickness, vegetative leaf temperature, plant height, panicle number, and tiller number) under heat stress conditions in both wet and dry seasons. Genes such as heat shock protein binding DnaJ, Hsp70, and temperature-induced lipocalin-2 OsTIL-2 close to these markers are candidates for expression studies and evaluation for use in marker assisted selection for heat tolerance.